(untitled) (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: The periodic medical examination is important in preventing some diseases and reducing their major complications; thus, it’s beneficial to provide a better healthy community and reducing financial loss. Studying beliefs, awareness, practice, and influence factors in the community will be a useful method to promote health among the population. Materials and Methods: Cross-sectional study survey in different areas in Makkah region using a sampling technique the sample size was 2061 participants of both gender. Data were collected through a self-administered structured survey. Results and Discussion: Adults 20–39 years (899) (56.9%) were the most group which have adequate knowledge. The most aware participants were females (928) (58.7%). 1021 (66.4%) of the aware participants have academic educational level. Most participants did not recall performing any medical checkup (1607) (78.0%). Conclusion: We noticed in this study that the rate of awareness of the participants was high but unfortunately it did not show reflection on their behavior toward medical checkups. This poor implementation despite their awareness was justified mostly by two major factors which were negligence and absence of motivation.